Identifikasi Mineralisasi Sulfida Menggunakan Metode Geolistrik 2D Resistivitas dan Induced Polarization (IP) Daerah Vulkanik Tolitoli, Sulawesi Tengah - Farah Dhiba; Amelia Oryza Sativa; Risky Martin Antosia; Nur Hidayat (Mataram University, 2026)
This study aims to identify indications of sulfide mineralization in the volcanic area of Tolitoli, Central Sulawesi, using two-dimensional (2D) geoelectrical resistivity and Induced Polarization (IP) methods. Data acquisition was carried out along ten survey lines using the Wenner–Schlumberger configuration, which were divided into two observation areas. The resistivity inversion results show relatively high values, generally exceeding 1000 Ωm, interpreted as massive and relatively fresh volcanic rocks such as andesite and basalt. Nevertheless, the Induced Polarization data reveal zones with moderate to high chargeability values (40–60 ms), indicating the presence of disseminated sulfide minerals, particularly pyrite, within the volcanic rocks. The chargeability anomalies are locally developed and are generally associated with fracture zones and geological structures that act as pathways for hydrothermal fluid migration. The most prominent prospective zones for sulfide mineralization were identified along survey lines 3 and 6. The integration of resistivity and IP methods is proven to be effective in identifying indications of sulfide mineralization in complex volcanic environments, even within high-resistivity rocks, and provides a preliminary assessment of subsurface mineralization potential in the Tolitoli area.